Growth and survival of Angelfish (Pterophyllum spp.) larvae raised under different diets - LP 5 FPSS 1 1994 (Universiti Pertanian Malaysia, 2012)
A study on growth and survival of angelfish (Pterophyllum spp.) larvae raised under different diets was carried out. The larvae for the above study were raised artificially. In order to achieve the abovementioned objective, four experiments were done.